Honeycomb boron carbon nitride as high-performance anode material for li-ion batteries - Karbhal, Indrapal; Chaturvedi, Vikash; Patrike, Apurva; Yadav, Poonam; Shelke, V, Manjusha (ChemNanoMat, 2022)
3D Porous carbon-based materials are well known for their excellent mechanical and electrochemical properties for various energy storage applications including Li-ion Battery (LIB) anodes. However, their commercial application is limited due to their low theoretical specific capacity. Heteroatom doping in carbonaceous networks proved an efficient way to modify the surface properties, which considerably improves the Li intake capacity and Li diffusion in porous carbon materials. In this work, we have synthesized 3D honeycomb boron carbon nitride (HBCN) from boric acid, glucose, and cyanamide. Silica nanoparticles (SiO2 NPs) are used as structure-directing agents to replicate well-organized honeycomb structures. HBCN possesses a high specific surface area (SSA) of similar to 597 m(2) g(-1), with a uniform porosity distribution, low charge transfer resistance, and steady Li flux. When analyzed as an anode material for LIB, HBCN demonstrated an excellent specific capacity of similar to 652 mAhg(-1) and 408 mAhg(-1) at an input current density of 100 mAg(-1) and 1 Ag-1 respectively and an energy density of 227 Wh kg(-1) at 1 C rate in a full cell LIB. These results indicate that the doping of B and N hetero atoms is significantly advantageous for LIBs application.
Keywords: 3D-Architecture; Heteroatom Doping; High-Performance Anode; Honeycomb boron carbon nitride (HBCN); Li-ion battery

High rate, high temperature, dendrite free plating/stripping of Li in 3-dimensional honeycomb boron carbon nitride to realize an ultrastable lithium metal anode - Patrike, Apurva; Karbhal, Indrapal; Wasnik, Kundan; Torris, Arun; Maibam, Ashakiran; Krishnamurty, Sailaja; Shelke, V, Manjusha (Journal of Energy Storage, 2023)
Lithium (Li) metal could be the anode of choice for energy dense Li-batteries owing to its high theoretical specific capacity. However, low coulombic efficiency and poor safety on account of the occurrence of the Li-dendrites during charging-discharging pose a bottleneck for practical applications. In this work, we report a high-rate plating and stripping of Li through host engineering to realize ultrastable Li metal anode (LMA). Benchmark plating/stripping efficiency could be achieved via uniquely structured, highly ordered honeycomb boron carbon nitride (HBCN) as a functional scaffold. Boron and nitrogen doping, large surface area and ordered mesoporous structure induce homogeneous solid electrolyte interface (SEI) layer formation and provide numerous nucleation sites with subsequent dendrite-free growth with 99.98 % coulombic efficiency at 8 mA cm(-2) high current and 10 mAh cm(-2) capacity over 3000 cycles. Via post-cycling advanced characterizations techniques of Ex-situ XPS, 3D X-ray micro-tomography analyses and FESEM, we demonstrate the formation of a stable SEI layer and morphological changes that occurred during Li plating cycles in the HBCN structure. Computational studies validate the high lithium plating-stripping efficacy of HBCN to its highly ordered porous nature, exothermic Li-binding and upshift in the Fermi levels. When tested at elevated temperature (50 degrees C), a stable Li plating-stripping in HBCN is realised at 4 mA cm(-2) current and 10 mAh cm(-2) capacity values with similar to 100 % C.E. Furthermore, we report the results of testing a Li metal cell comprised of Li deposited HBCN anode and LiFePO4 (LFP) cathode.
Keywords: Boron carbon nitride; Dendrite-free Li metal anode; Functional scaffold; High temperature plating/stripping of Li; Molecular planarity parameter; X-ray micro-tomography